Notes on Relative Contact Equivalence of Complex Analytic Map-Germs - Al-Bahadeli, Mohammed S. J. (Iraqi Journal of Science, 2022)
In these notes, our goal is to give some results on criterion for complex analytic map-germs by their tangent spaces with respect to -equivalence where is the module of complex analytic vector fields on .In addition, we give some results about -trivial analytic family, the direct product and direct sum of map-germs.